Optimasi Pengolahan Leachate Dengan Kombinasi Biofilter Dan Fitoremediasi Berbasis Tanaman Bambu Air Untuk Menurunkan Kadar Logam Cr - Widyastuti, Diena; Zairina, Anisa; Suprayitno, Didik; Sulastri, Sri; Mondiana, Yani Quarta (JURNAL GREEN HOUSE, 2025)
Leachate from landfill sites contains heavy metals such as chromium (Cr), which are toxic and carcinogenic, requiring effective management to prevent environmental contamination. This study aimed to optimize the reduction of Cr levels in leachate using a combination of biofilter and phytoremediation based on aquatic bamboo plants. The research was conducted at the Laboratory and Greenhouse of Institut Pertanian Malang using a Completely Randomized Design (CRD) with two treatments (biofilter only and biofilter combined with phytoremediation) and five replications. The biofilter utilized natural media including gravel, silica sand, coconut shell charcoal, and compost, while phytoremediation employed aquatic bamboo (Equisetum hyemale). Results showed that Cr levels decreased from 3.89 mg/L to 2.20 mg/L with biofilter treatment alone, and further decreased to 1.08 mg/L when using the combined biofilter-phytoremediation treatment, with removal efficiencies of 43.4% and 72.8%, respectively. The most significant reduction occurred during the initial weeks, followed by a gradual decline towards the end of the observation period. The combination of biofilter and phytoremediation with aquatic bamboo proved effective and environmentally friendly in reducing Cr levels in leachate, indicating its potential for broader application in leachate management at landfill sites